Health literacy and patient activation among adults with chronic diseases in Singapore: A cross‐sectional study - Laura Yuqi Huang; Yongxing Patrick Lin; George Frederick Glass Jr; Ee‐Yuee Chan (Wiley, 2021)
Abstract Aims Increased patient activation levels can improve health outcomes. Hence, this study aims to examine the relationships between sociodemographic variables and domain‐specific health literacies with patient activation. Design A cross‐sectional design. Methods 200 outpatient adults with chronic diseases completed a survey that assessed their domain‐specific health literacy and patient activation levels. Univariate and multivariate analysis of the variables were conducted on patient activation with 95% confidence interval (CI). Results Multiple linear regression analyses observed a positive linear relationship between the following domain‐specific health literacy variables-"actively manage my health" (p < .0001, 95% CI: 0.89-2.29), "understanding health information" (p = .008, 95% CI: 0.28-1.85), and "finding good health information" (p = .02, 95% CI 0.13-1.51) with patient activation. The other sociodemographic and clinical variables were not statistically significant. Increased focus from healthcare professionals is needed on helping patients better find and understand health information and encouraging them to actively manage their health; elements which would raise their activation levels.